(untitled) (SciComm Report, 2021)
The communication will describe the process of scientific dissemination led by a team of Chilean girl researchers based on the support of the Think Big Chile project, which, in turn, promotes health and wellness initiatives led by children and young people. This would be reflected in the collective elaboration, between adult and female researchers, of this communication. The methodology, of the preparation of the dissemination of results and their participation as such in the Tour, was qualitative. The research techniques were semi-structured group interviews and international meetings, both remotely via Zoom. As a result of those interviews, it was possible to generate a collective interpretation of the results of the national application of an instrument for measuring participation and other rights, previously created by NNJ during the Think Big Chile study, and the description of their educational experience during the COVID-19 virus pandemic. It is expected to generate an approach to the experience of disseminating the results from the perspective of the participating girls and to present some reflections of the process from the perspective of the adult facilitator